Fundus findings in patients with type I diabetes mellitus - Akarsu, Saadet; Sen, Yasar; Yilmaz, Turgut; Kurt, Abdullah; Girgin, Feyza Incekoy (Aves, 2006)
Aim: While juvenile diabetics are followed more regularly, the importance of retinopathy in diabetic children is generally underestimated. Ophthalmologic examination may present some differences in patients with Type I diabetes mellitus (IDDM) according to the age of the patient. The effectiveness of blood-retina barrier is stable in patients with IDDM until the age of puberty. A progressive decrease is observed in the blood-retina barrier after this period. The diabetic retinopathy is a kind of microangiopathy which can lead to blindness. Patients with IDDM should be followed regularly with a retinal examination, starting 3-5 years after the first diagnosis. In this study, we presented the fundus findings of our cases with post-pubertal IDDM. Material and Method: A total of 53 patients with IDDM who had been followed for more than a year were evaluated by an ophthalmologist. Visual acuity of the patients was determined by using Snellen test. Biomicroscobic examination of the frontal segment, indirect ophthalmoscopy following pupillary dilatation and retina examinations were performed. Results: The mean age of the patients and the duration of the disease were 15.3 and 5.1 years, respectively. The mean visual acuity was 86.6% in the right and 85.2% in the left eyes. Ophthalmoscopic examination revealed a normal left and right fundus in 33 (62.3%) and 34 (64.1%)of the patients, respectively. Four patients (7.5%) developed a background retinopathy. These patients were those who were followed less than five years. Non-proliferative retinopathy was observed in only one patient (1.9%) who had been followed for a period of 15 years. Proliferative retinopathy was recorded in three patients (5.7%) who were followed for more than five years. Edema of the macula and optic atrophy were detected in eight (15.1%) and three patients (5.7%), respectively. Three patients had cataract (5.7%), of these two (66.7%) had been followed over 10 years. Conclusions: The retinopathy incidence in IDDM patients increases when the duration of the disease is prolonged. Examination of the retina and periodic follow-up are of importance in terms of protection and maintenance of the visual functions.
Tip I diabetes mellitus hastalarinda fundus bulgulari
Keywords: Childhood; diabetes; fundus; retinopathy